2023
DOI: 10.3390/ijms24031915
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Molecular Imprinting: Strategies, Applications and Determination of Target Molecules in Spain

Abstract: Over the last decades, an increasing demand for new specific molecular recognition elements has emerged in order to improve analytical methods that have already been developed in order to reach the detection/quantification limits of target molecules. Molecularly imprinted polymers (MIPs) have molecular recognition abilities provided by the presence of a template molecule during their synthesis, and they are excellent materials with high selectivity for sample preparation. These synthetic polymers are relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Molecularly imprinted polymers (MIPs) are synthesized using molecular imprinting technology, in which functional monomers are allowed to self-assemble around a template molecule and are subsequently polymerized in the presence of a crosslinker. After completion of polymerization, the templates are removed, providing tailor-made binding sites or artificial receptors that have complementary shapes, sizes, and functionalities toward the target template [13]. Compared to traditional sorbents, MIPs offer good mechanical/chemical stability, high specificity, low-cost, easy preparation, and reversible adsorption/release of the target molecule, enabling selective sample extraction and preconcentration.…”
Section: Introductionmentioning
confidence: 99%
“…Molecularly imprinted polymers (MIPs) are synthesized using molecular imprinting technology, in which functional monomers are allowed to self-assemble around a template molecule and are subsequently polymerized in the presence of a crosslinker. After completion of polymerization, the templates are removed, providing tailor-made binding sites or artificial receptors that have complementary shapes, sizes, and functionalities toward the target template [13]. Compared to traditional sorbents, MIPs offer good mechanical/chemical stability, high specificity, low-cost, easy preparation, and reversible adsorption/release of the target molecule, enabling selective sample extraction and preconcentration.…”
Section: Introductionmentioning
confidence: 99%
“…Manipulation with an external magnetic field opens the possibility of unique applications for MMIPs, which may be used for solid-phase extraction of pollutants in water samples (pesticides, herbicides, antibiotics, dyes, heavy metals, etc.) [7,8,12,[15][16][17][18][19][20][21][22][23][24], photocatalytic and dark-condition degradation of pollutants [23], isolating active compounds contained in plants (alkaloids, flavonoids, terpenes, etc.) [12], enantioseparation [25], and the separation, purification, and detection of various biomolecules [22,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…[7,8,12,[15][16][17][18][19][20][21][22][23][24], photocatalytic and dark-condition degradation of pollutants [23], isolating active compounds contained in plants (alkaloids, flavonoids, terpenes, etc.) [12], enantioseparation [25], and the separation, purification, and detection of various biomolecules [22,[26][27][28]. MMIPs show excellent selective binding to target compounds and can be quickly separated and easily removed from samples using an external magnet, thus avoiding time-consuming and tedious steps (centrifugation or filtration) [7,8,12,[18][19][20][21][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous comprehensive reviews published in recent years have thoroughly discussed the application capabilities of different MIPs in the molecular imprinting field [18][19][20][21][22][23][24]. However, none of these reviews has demonstrated the role of yeast in molecular imprinting.…”
Section: Introductionmentioning
confidence: 99%